Speaking English as Experienced by Grade 7 Students: A Phenomenological Study - Kathleen Rivera; Haydee Villanueva (EduLine: Journal of Education and Learning Innovation, 2023)
Speaking the English language can be difficult for some second-language learners. This study explored the difficulties and experiences of using the English language among selected Grade 7 students in one of the private institutions in Ozamiz City, Philippines. The study used the phenomenological research design. Six students served as the study's participants and were selected through the purposive sampling technique. Research-made Interview Guide was used in gathering the data. The Moustakas' steps of data analysis were used in analyzing the data gathered. The study yielded four themes, namely: speaking difficulties experienced, psychological effects during class, adverse outcomes of speaking difficulties, and coping with English-speaking difficulties. The participants experienced recurrent deficiencies in the target language and struggled to perform oral activities in their English classes. The English-speaking difficulties deeply impact language learners, but they endeavor to overcome their linguistic limitations. Thus, attaining a good proficiency in the English language entails recognizing the difficulties and exerting the necessary effort to overcome them.